2017
DOI: 10.3390/ijms18061168
|View full text |Cite
|
Sign up to set email alerts
|

Can Co-Activation of Nrf2 and Neurotrophic Signaling Pathway Slow Alzheimer’s Disease?

Abstract: Alzheimer’s disease (AD) is a multifaceted disease that is hard to treat by single-modal treatment. AD starts with amyloid peptides, mitochondrial dysfunction, and oxidative stress and later is accompanied with chronic endoplasmic reticulum (ER) stress and autophagy dysfunction, resulting in more complicated pathogenesis. Currently, few treatments can modify the complicated pathogenic progress of AD. Compared to the treatment with exogenous antioxidants, the activation of global antioxidant defense system via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 236 publications
(258 reference statements)
2
32
0
Order By: Relevance
“…The neurotrophic effect of midi-GAGR appears to partly contribute to its neuroprotective effect ( 28 ), although it might not be sufficient enough to offer neuronal protection against oxidative stress. Given that antioxidant enzymes are the major endogenous defense system to scavenge free reactive radicals ( 1 ), it is possible that antioxidant enzymes might be increased by the low-acyl gellan gum cleavage product, mini-GAGR. To examine this possibility, we tested the effect of mini-GAGR on the protein levels of several major antioxidant enzymes in mouse embryonic cortical neurons (E17, DIV11–14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The neurotrophic effect of midi-GAGR appears to partly contribute to its neuroprotective effect ( 28 ), although it might not be sufficient enough to offer neuronal protection against oxidative stress. Given that antioxidant enzymes are the major endogenous defense system to scavenge free reactive radicals ( 1 ), it is possible that antioxidant enzymes might be increased by the low-acyl gellan gum cleavage product, mini-GAGR. To examine this possibility, we tested the effect of mini-GAGR on the protein levels of several major antioxidant enzymes in mouse embryonic cortical neurons (E17, DIV11–14).…”
Section: Resultsmentioning
confidence: 99%
“…Because Nrf2 is the major transcriptional factor for the expression of antioxidant enzymes ( 1 ), it is possible that mini-GAGR, which increases antioxidant enzymes, activates Nrf2 in mouse cortical neurons. First, we examined whether mini-GAGR induced the nuclear translocation of Nrf2 in mouse cortical neurons (E17, DIV11–14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that stimulation of the BDNF/PI3K/Akt signaling pathway leads to the inhibition of GSK-3β phosphorylation [ 19 ]. Moreover, activation of the BDNF/PI3K/Akt signaling pathway suppresses oxidative stress caused by Aβ peptides [ 43 ]. Thus, we investigated the BDNF/PI3K/Akt signaling pathway to further examine the association between BDNF and oxidative stress induced by Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is one of the important characteristics of AD-resulting brain damage, and oxidative stress can be altered by the Nrf2-ARE antioxidant pathway. This pathway can be activated by a number of natural products especially the flavonoids and nonflavonoid polyphenols (Murphy & Park, 2017). The essential oil of Su He Xiang Wan (SHXW), a traditional Chinese medicine, has been showed to suppress Aβ-induced apoptosis and ROS production through upregulation of Nrf2 and HO-1 expression in SH-SY5Y cells.…”
Section: Admentioning
confidence: 99%